Long-term effect of sildenafil on echocardiographic parameters in dogs with asymptomatic myxomatous mitral valve degeneration - Kijtawornrat A. (2017)
© 2017 The Japanese Society of Veterinary Science. Sildenafil is a selective phosphodiesterase-5 inhibitor that has been demonstrated to delay ventricular remodeling in humans and experimental animals. The aim of this prospective study was to assess the chronic effects of sildenafil administration on echocardiographic indices and N-terminal pro-B-type natriuretic peptide (NT-proBNP) in dogs with naturally occurring, asymptomatic myxomatous mitral valve degeneration. Thirty client-owned dogs with ACVIM class B1 or B2 were enrolled. Dogs were randomly assigned to treatment (sildenafil 1–3 mg/kg, PO, BID for 180 days) or control groups. A total of 12 dogs completed the 180 days trial in the sildenafil group, whereas 10 dogs remained in control group. When comparing the difference from baseline values obtained over time between groups, the stroke volume (SV) at day 30 was significantly higher in the sildenafil group (P=0.038). The LA/Ao and the MR jet area were significantly lower beginning at day 30 (only MR jet area; P=0.006), day 90 (P=0.006 and P=0.027, respectively) and day 180 (P=0.029 and P=0.032, respectively). The 2D-LA was significantly lower at day 90 when compared with control group (P=0.028). The differences of NTproBNP from baseline were significantly lower when compared with control group at the same timepoint (D90, P=0.017 and D180, P=0.013). In conclusion, this study suggested that long-term treatment with sildenafil prevented aggravation of disease progression as suggested by several echocardiographic indices (i.e. SV, LA/Ao, MR jet area, 2D-LA) and reduced NTproBNP level at the indicated timepoints in dogs with asymptomatic mitral valve degeneration.